Update of the EAU/ESPU guidelines on urinary tract infections in children. Issue 2 (April 2021) - 't Hoen, Lisette A.; Bogaert, Guy; Radmayr, Christian; Dogan, Hasan S.; Nijman, Rien J.M.; Quaedackers, Josine; Rawashdeh, Yazan F.; Silay, Mesrur S.; Tekgul, Serdar; Bhatt, Nikita R.; Stein, Raimund
Summary: Introduction/background: Urinary tract infections (UTIs) are common in children and require appropriate diagnostic evaluation, management and follow-up. Objective: To provide a summary of the updated European Association of Urology (EAU) guidelines on Pediatric Urology, which were first published in 2015 in European Urology. Study design: A structured literature review was performed of new publications between 2015 and 2020 for UTIs in children. The guideline was updated accordingly with relevant new literature. Results: The occurrence of a UTI can be the first indication of anatomical abnormalities in the urinary tract, especially in patients with a febrile UTI. The basic diagnostic evaluation should include sufficient investigations to exclude urinary tract abnormalities, but should also be as minimally invasive as possible. In recent years, more risk factors have been identified to predict the presence of these anatomical anomalies, such as a non-E. Coli infection, high grade fever and ultrasound abnormalities. When these risk factors are factored into the diagnostic work-up, some invasive investigations can be omitted in a larger group of children. In addition to the treatment of active UTIs, it is also essential to prevent recurrent UTIs and consequent renal scarring. With the increase of antimicrobial resistance good antibiotic stewardship is needed. In addition, alternative preventative measures such as dietary supplements, bladder and bowel management and antibiotic prophylaxis could decrease the incidence of recurrent UTI. Conclusion: This paper is a summary of the updated 2021 EAU guidelines on Pediatric Urology. It provides practical considerations and flowcharts for the management and diagnostic evaluation of UTIs in children.